Structural and Electronic Effects of Incorporating Mn in TiO2 Films Grown by Sputtering: Anatase versus Rutile - Pereira, Andre L. J. [UNESP]; Gracia, Lourdes; Beltran, Armando; Lisboa Filho, Paulo Noronha [UNESP]; Silva, Jose H. D. da [UNESP]; Andres, Juan (Amer Chemical Soc, 2012)
Pure and Mn-doped TiO2 films have been deposited by sputtering technique onto SiO2 substrates. The films display a compact columnar morphology, as revealed by scanning electron microscopy. X-ray diffraction and Raman scattering results provide evidence that the pure TiO2 films are predominantly anatase phase, but the increase in Mn concentration favors the rutile phase. The optical characterization shows a systematic decrease in the value of band gap and an increase in the tail states with the increase in Mn concentration. Magnetization measurements display purely diamagnetic behavior in the undoped TiO2 film and substrate and paramagnetic behavior in the Mn-doped films. No indication of ferromagnetic signature has been evidenced. First-principle calculations based on density functional theory and periodic models were employed to calculate the band structure and the density of electronic states to investigate the influence of Mn incorporation in the electronic structure of TiO2. Both experimental data and electronic structure calculations evidence the fact that the presence of Mn produces important modifications in the electronic states, mainly related to the 3d Mn orbitals in the inside the gap and in the vicinity of the band edges.